2014
DOI: 10.1111/bph.12842
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the binding mode for the cyclopentapeptide CXCR4 antagonist FC131 using a dual approach of ligand modifications and receptor mutagenesis

Abstract: BACKGROUND AND PURPOSEThe) is an antagonist at the CXC chemokine receptor CXCR4, which plays a role in human immunodeficiency virus infection, cancer and stem cell recruitment. Binding modes for FC131 in CXCR4 have previously been suggested based on molecular docking guided by structure-activity relationship (SAR) data; however, none of these have been verified by in vitro experiments. EXPERIMENTAL APPROACHHeterologous 125 I-12G5-competition binding and functional assays (inhibition of CXCL12-mediated activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 60 publications
8
66
0
Order By: Relevance
“…Importantly, none of these studies were accompanied by in vitro experiments that verified the proposed binding mode. However, a recent binding mode study of FC131 based on extensive site--directed mutagenesis [104] supports the previously suggested binding models. The collective picture that has emerged from these models is generally consistent with SAR (see section Figure 6A) [105].…”
Section: Binding Modesupporting
confidence: 63%
“…Importantly, none of these studies were accompanied by in vitro experiments that verified the proposed binding mode. However, a recent binding mode study of FC131 based on extensive site--directed mutagenesis [104] supports the previously suggested binding models. The collective picture that has emerged from these models is generally consistent with SAR (see section Figure 6A) [105].…”
Section: Binding Modesupporting
confidence: 63%
“…23,33,58 However, the R188A mutation did not have any effect on the antagonistic potency of 1 or the two analogs (Table 2); interestingly, the R188A-mutant was also reported to have no effect on the potency of FC131. 35 A possible explanation is that both 1 and FC131 are doubly positively charged, which results in electrostatic repulsion by Arg 188 .…”
Section: Displacement Of Radiolabeled Monoclonal Antibody ( 125 I-12g5)mentioning
confidence: 99%
“…35 and 1 inhibit binding of the same set of monoclonal antibodies, directed against the extracellular loops of CXCR4, it has been suggested that they have similar binding sites and molecular mode of action. 28,65 As Asp 171 , Asp 262 , and indirectly Glu 288 are also involved in binding of 1 (Figure 6), the present study confirms that these two compounds bind to the same receptor region.…”
Section: Comparison With Experimentally Determined Binding Modes Formentioning
confidence: 99%
See 1 more Smart Citation
“…Unless otherwise stated, 100% accounts for the maximal chemokine-induced response observed at the given mutant, or WT when chemokines were inactive at the mutant, and 0% is the signaling of the given receptor (mutant or WT) in the absence of any ligand. These overall readouts have previously been used effectively for CCR5, CXCR4, and other chemokine receptors (21,22,59,60).…”
Section: Methodsmentioning
confidence: 99%